Digital Dynamics in Public Discourse: Analyzing the Relationship Between Digital Media and Counter-Public Spheres - Özgün Dinçer (Yeni Medya)
The main aim of the study is to investigate the question of whether digital media encourages the expansion of the counter-public spheres by allowing greater participation and representation, or whether it leads to fragmentation and polarization. While digital media is welcomed for providing spaces for marginalized communities to express themselves, there are also concerns about the isolation and fragmentation of the public sphere, such as creating echo chambers and filter bubbles. This study aims to contribute to this ongoing debate by employing thematic analysis of recent empirical research in literature. By examining studies on various online activities related to counter-public spheres across different countries, this research analyzes the current situation in the literature concerning digital media’s impact on the public sphere. Moreover, a comparative study of conditions in different countries also allows the identification of common patterns and differences in how digital media shapes opposing activities in diverse cultural, political and social contexts. Additionally, the research reveals the prevailing approaches and gaps in the literature.